A comprehensive analysis of erectile dysfunction prevalence and the impact of prostate conditions on ED among US adults: evidence from NHANES 2001-2004 - Zhang, Yuhao; Zang, Nan; Xiang, Yingyue; Lin, Fanlu; Liu, Xue; Zhang, Jing (Frontiers in Endocrinology, 2025)
BackgroundErectile dysfunction (ED) is characterized by the inability to achieve or maintain penile erection sufficient for intercourse. While previous research suggests a potential link between ED and prostate pathologies, the association between benign prostatic hyperplasia (BPH), prostatitis, prostatic cancer (PCa), and ED remains to be elucidated.MethodsData from participants (40-80 years, n=2225) were extracted from the NHANES 2001-2004 for this observational study. The investigation encompassed the following aspects: assessment of ED prevalence within subgroups, comparison of baseline characteristics between individuals with and without ED, analysis of associations between BPH, prostatitis, PCa, and ED using multivariable weighted logistic regression in the 40-60 and 60-80 age groups and subgroup analysis based on body mass index, hypertension, diabetes, and smoking status.ResultsAmong the 2225 participants, the weighted prevalence of ED was 27.47%, with 16.17% in the 40-60 years age group and 56.98% in the 60-80 years age group. BPH had an ED prevalence of 47.57%, prostatitis 34.62%, and PCa 85.62%. Comparative analysis between ED and non-ED groups revealed significant differences in education levels, PIR, smoking and alcohol status, creatinine, total cholesterol, LDL cholesterol, diabetes, hypertension, BPH, and PCa. Multivariate logistic regression analysis identified BPH as an independent risk factor for ED in the 60-80 years age group (OR=1.93; 95% CI, 1.18-3.18, P=0.02), and PCa was positively associated with ED in both the 40-60 years group (OR=11.90; 95% CI, 1.41-100.50, P=0.03) and the 40-80 years group (OR=7.30; 95% CI, 2.12-25.08, P=0.01). No clear correlation was found between prostatitis and ED. Subgroup analyses indicated that the association between BPH and ED was significant in non-diabetic, overweight/obese, and smoking groups, while the association between PCa and ED was more pronounced in non-diabetic, hypertensive individuals across all body mass index (BMI) categories, and in both smoking and non-smoking groups. Prostatitis showed no significant relationship with ED in any subgroup.ConclusionThe study established BPH and PCa as significant risk factors for ED, with no substantial link detected between prostatitis and ED. This finding highlights the necessity for tailored screening and management protocols for individuals with BPH and PCa to mitigate the burden of ED.